1995
DOI: 10.1073/pnas.92.13.6072
|View full text |Cite
|
Sign up to set email alerts
|

Regulated assembly of tight junctions by protein kinase C.

Abstract: We have previously shown that protein phosphorylation plays an important role in the sorting and assembly of tight junctions. We have now examined in detail the role of protein kinases in intercellular junction biogenesis by using a combination of highly specific and broad-spectrum inhibitors that act by independent mechanisms. Moreover, membrane-associated PKC activity more than doubled during junction assembly, and immunocytochemical analysis revealed a pool of PKC C that appeared to colocalize with ZO-1 at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
182
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(200 citation statements)
references
References 20 publications
17
182
1
Order By: Relevance
“…Chasiotis and Kelly [50] reported that high levels of cortisol can upregulate claudin 7 and occludin mRNA expression in goldfish gills. Furthermore, TJ expression can be regulated by PKC signalling pathways in terrestrial animals [25]. Yamaguchi, Kojima [53] showed that inhibition of PKC reduced claudin 7 and occludin expression in human pancreatic duct epithelial cells.…”
Section: Arginine Improved the Intestinal Barrier Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chasiotis and Kelly [50] reported that high levels of cortisol can upregulate claudin 7 and occludin mRNA expression in goldfish gills. Furthermore, TJ expression can be regulated by PKC signalling pathways in terrestrial animals [25]. Yamaguchi, Kojima [53] showed that inhibition of PKC reduced claudin 7 and occludin expression in human pancreatic duct epithelial cells.…”
Section: Arginine Improved the Intestinal Barrier Functionmentioning
confidence: 99%
“…The above information indicated that arginine may have an effect on fish intestinal TJs. Furthermore, a central role for protein kinase C (PKC) in the regulation of TJ expression has emerged in terrestrial animals [25]. However, information regarding the effect of arginine on PKC signalling in fish is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, several studies have demonstrated the involvement of various kinases in the phosphorylation and regulation of claudin proteins [29][30][31][32][33][34][35][36][37], and we have recently shown that phosphorylation of claudin-3 by PKA can affect TJ properties in ovarian cancer cells [38]. Protein kinase C (PKC) isoforms are present in ovarian cancer and are known to modulate TJ function by phosphorylation of the proteins in the complex [24,34,[39][40][41][42][43], but it is unclear whether PKC can directly phosphorylate and regulate claudin proteins. We have previously shown that claudin-4 can be phosphorylated in ovarian cancer cells upon 12-OTetradecanoylophorbol-13-acetate (TPA) stimulation [38], but the exact PKC isoforms involved, the phosphorylation sites on claudin-4, and the consequences of this phosphorylation have remained unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The use of specific inhibitors has implicated conventional PKC (cPKC) in regulating assembly of TJs (60). In fact, ZO-1 has been shown to be a cPKC substrate (60).…”
Section: Jam-a Phosphorylation and Kinases Are Important For Epithelimentioning
confidence: 99%